The Pharmacological Mechanism of Guchangzhixie Capsule Against Experimental Colitis - Yan, Jing; Yu, Wei; Lu, Chang; Liu, Chen; Wang, Guoliang; Jiang, Lu; Jiang, Zizheng; Qin, Zheng (Frontiers in Pharmacology, 2021)
Ulcerative colitis (UC) is the major type of inflammatory bowel disease (IBD) characterized by an overactive immune response and destruction of colorectal epithelium with intricate pathological factors. Guchangzhixie (GCZX) capsule, included in the Chinese Pharmacopoeia 2020, has been widely utilized against UC. However, the underlying molecular mechanisms have not been elucidated. In the present study, a murine model of experimental colitis was established by orally feeding 4% dextran sodium sulfate (DSS) for 5 days and subsequently subjected to GCZX treatment for another 15 days. Network pharmacology analysis was performed to predict the pertinent mechanisms of GCZX capsule. Cellular experiments examining the functional changes of intestinal organoids (IOs), macrophages (Mφs) and human colon epithelial cell cells (NCM460 cell line) after GCZX therapy were performed. 16S rRNA sequencing was conducted on the stools from the mouse model. Liquid chromatography-mass spectrometry (LC–MS) was utilized to detect serum metabolites. As a result, DSS induced experimental colitis and this induction was alleviated by GCZX treatment, as evidenced by rescued pathological symptoms in UC mouse models, such as rectal bleeding stopping, decreased levels of albumin, interleukin-17 as well as CXCL1, and reduction in colon length. Network pharmacology analysis showed that GCZX-target genes were enriched in pathogen-induced infections, inflammatory pathways as well as neoplastic processes. DSS treatment decreased microbial diversity and led to the accumulation of pathological bacterial, which was reversed by GCZX capsule. PICRUSt2 (Phylogenetic Investigation of Communities by Reconstruction of Unobserved States) based on profiles of microbiota composition demonstrated a decreased incidence of infectious disease and cancers after GCZX therapy. In full accordance with these data, GCZX administration suppressed Mφ transition to pro-inflammatory phenotype, alleviated tumor necrosis factor-α (TNFα)-compromised IOs functions and decreased the recruitment of Mφs by epithelial cells. We conclude that GCZX capsule is an effective drug for UC and its pharmacological mechanisms involve re-establishing an anti-inflammatory milieu and favoring mucosal healing.